2009
DOI: 10.1063/1.3098357
|View full text |Cite
|
Sign up to set email alerts
|

Strong terahertz radiation from air plasmas generated by an aperture-limited Gaussian pump laser beam

Abstract: Terahertz radiation generated by focusing the fundamental laser pulse and its second harmonic into ambient air strongly saturates with increasing pump laser energy. We demonstrate a simple method to control the Gaussian pump laser beam to improve the output of terahertz radiation with an adjustable aperture. With the optimal aperture-limited pump laser beams, the terahertz wave amplitudes can be enhanced by more than eight times depending on the pump laser parameters than those of aperture-free cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Furthermore, the generated THz radiation strongly saturates with increasing pump laser energy. Using an aperture to limit the pump laser beam, the amplitude of THz radiation can be enhanced more than eight times of that in aperture-free cases [68].…”
Section: Terahertz Sources Based On Plasmamentioning
confidence: 99%
“…Furthermore, the generated THz radiation strongly saturates with increasing pump laser energy. Using an aperture to limit the pump laser beam, the amplitude of THz radiation can be enhanced more than eight times of that in aperture-free cases [68].…”
Section: Terahertz Sources Based On Plasmamentioning
confidence: 99%
“…The THz wave amplitude from a two-color filament can also be enhanced by more than eight times with an optimal aperture-limited pump laser beam according to Ref. [18] by Peng et al Replacing the focusing lens with a gold off-axis parabolic mirror, Blanchard et al reported more than 2 times increase in THz generation efficiency from two-color plasma [19] . More recently, by using a converging lens followed by an axicon resulting in a tailored two-color laser filament in air, Manceau et al reported significant THz temporal pulse shortening from a uniform plasma strings [20] .…”
Section: Thz Generation From Femtosecond Laser Filamentationmentioning
confidence: 99%
“…THz electric field as high as 400 kV/cm [19] and a super-broadband THz spectrum up to 75 THz (λ = 4 μm) with μJ pulse energy [20,21] were reported. Several techniques based on the two-color laser-induced filamentation such as applying a DC field along two-color filaments [22], the control of multiple air plasmas [23,24], pump beam size [25] and pump pulse chirp [21] have been reported to • dichroic mirrors, which have high reflectivity around 400 nm and a high transmission around 800 nm. QWP and HWP are quarter wave plate and half wave plate, respectively.…”
Section: Introductionmentioning
confidence: 99%